(untitled) (Orfeu, 2022)
Transcribing or arranging pieces from other instruments and/or formations has been a very common guitar practice in Brazil since the 19th century. In dialogue with part of the available bibliography and presenting primary sources, this article traces a brief historical overview of transcriptions and arrangements for guitar, seeking to understand some of the sociocultural functions that this adapted repertoire had in the Brazilian case, especially in the passage between the 19th and 20th centuries. Taking as an object of study two transcriptions of romantic authors (Chopin and Massenet) made by Melchior Cortez (1882-1947), the results suggest that there was an effort to incorporate concert music canons into the guitar literature, with the aim of reveal its potential and demonstrate that the instrument could serve any repertoire, including “the great classics performed on its six simple strings.” (O VIOLÃO, 1928, p. 3).